The Association of Vitamin D with Metabolic Syndrome in Adults with Prediabetes - Morshed, Md Shahed; Haq, Tahniyah; Selim, Shahjada; Ghani, Habibul; Faisal, Ibrahim; Yadav, Anil; Shah, Anil Kumar; Md Fariduddin, - (Bangladesh Journal of Medicine, 2021)
Background: Vitamin D may play important role in the pathogenesis of several components of metabolic syndrome (MS). The aim of this study was to observe the association of vitamin D with MS and its components in Bangladeshi adults with prediabetes. Methods: This cross-sectional study was done among 117 newly detected nonpregnant adults with prediabetes [age (years): 36.30±9.99; BMI (kg/ m2): 28.89±4.35, mean±SD; M/F: 23/94] based on American Diabetes Association 2018 criteria. Metabolic syndrome was diagnosed by any three of five criteria: central obesity; elevated blood pressure, fasting blood glucose & triglyceride (TG) and lower HDL cholesterol. Glucose was measured by glucose oxidase, lipid by glycerol phosphate dehydrogenase-peroxidase and vitamin D by high performance liquid chromatography method. Vitamin D <20 ng/ml was considered as deficiency (VDD). Results: Among all the variables only TG was significantly higher in patients with VDD than those without VDD (³20 ng/ml) [163.0 (135.50, 224.50) vs. 143.50 (101.25, 190.0), median (IQR), p=0.048]. There were no significant correlations [p=NS for all] and associations of vitamin D with MS or its components in linear and logistic regression [p=NS for all]. Conclusions: Except TG vitamin D has no associations with MS or its components in Bangladeshi adults with prediabetes. Bangladesh J Medicine July 2021; 32(2) : 170-174